Evaluation of high-energy calf starter for early-weaned calves - W.H. Carinder; P.G. Reddy; J.L. Morrill (Kansas Agricultural Experiment Station Research Reports, 1986)
An experimental calf-starter diet containing roasted whole soybeans, buffer and dehydrated alfalfa pellets was compared with a conventional calf starter for young calves on an early-weaning program. Overall means for weight gains, dry feed consumption, and fecal scores were similar for the two treatments. However, calves fed the experimental calf starter showed a trend toward higher gains at 4 and 5 wk of age. More fat than necessary in the diet and feeding of prestarter until 8 wk of age may have precluded finding significant benefits with the experimental starter.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; High energy calf starter; Gain; Feed consumption; Fecal scores